(untitled) (Global Journal of Science Frontier Research, 2021)
In this paper, we introduces a new distribution called Type II half logistic exponentiated lomax (TIIHLEE) distribution established from Type II half logistic G family of distribution We investigate some of its mathematical and statistical properties such as the explicit form of the ordinary moments, moment generating function, conditional moments, mean deviations, residual life and Renyi entropy. The maximum likelihood method is used to estimate the model parameters. Simulation studies were conducted to assess the finite sample behavior of the maximum likelihood estimators. Finally, we illustrate the importance and applicability of the model by the study of two real data sets.